2022
DOI: 10.3390/catal12080928
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid/Deep Eutectic Solvent-Mediated Ni-Based Catalysts and Their Application in Water Splitting Electrocatalysis

Abstract: Nickel-based electrocatalysts have been widely used to catalyze electrocatalytic water splitting. In order to obtain high-performance nickel-based electrocatalysts, using ionic liquids and deep eutectic solvents mediated their preparation has received increasing attention. Firstly, ionic liquids and deep eutectic solvents can act as media and templates for the preparation of Ni-based nanomaterials with novel structures and excellent catalytic activity. Secondly, ionic liquids and deep eutectic solvents can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…Through the additional properties that NDESs possess, their applications are constantly expanding. Currently, the main research efforts are concentrated in areas such as biomedicine, metal treatment and extraction of a series of compounds, metallurgy, electrodeposition, separations, gas capture and biocatalysis [ 15 , 20 , 58 , 59 , 60 ]. Nanotechnology is a new field in which NDESs may find an application ( Figure 6 ).…”
Section: Natural Deep Eutectic Solvents Applications In Nanotechnologymentioning
confidence: 99%
See 1 more Smart Citation
“…Through the additional properties that NDESs possess, their applications are constantly expanding. Currently, the main research efforts are concentrated in areas such as biomedicine, metal treatment and extraction of a series of compounds, metallurgy, electrodeposition, separations, gas capture and biocatalysis [ 15 , 20 , 58 , 59 , 60 ]. Nanotechnology is a new field in which NDESs may find an application ( Figure 6 ).…”
Section: Natural Deep Eutectic Solvents Applications In Nanotechnologymentioning
confidence: 99%
“…Additionally, depending on the choice of NDES, we can base the solution on specific parameters, i.e., viscosity, pH, refractive index, etc., which, depending on the future applications of the material, can be crucial. The composition of NDESs and their form, especially at the beginning of their applications in nanotechnology, was used as a reaction medium in electrochemical processes to obtain a range of nanomaterials [ 60 , 61 ].…”
Section: Natural Deep Eutectic Solvents Applications In Nanotechnologymentioning
confidence: 99%
“…Abundant hydrogen bond donors can provide an effective way for proton conduction. Abundant hydrogen bond donors/receptors can provide efficient pathways for proton transport, reducing energy losses during the proton transfer process in batteries and leading to improved efficiency of the battery [64–65] . Chaabene et al.…”
Section: Compositions and Types Of Electrolytesmentioning
confidence: 99%
“…Abundant hydrogen bond donors/receptors can provide efficient pathways for proton transport, reducing energy losses during the proton transfer process in batteries and leading to improved efficiency of the battery. [64][65] Chaabene et al tested the decomposition voltage and ionic conductivity of a series of electrolytes with ionic liquids as solvents and found that the electrolyte composed of 2 M acetic acid (Ac.A) added to 1-ethyl-3-methylimidazolium acetate([EMIM][Ac] + Ac.A (2 M)) showed a wide operating voltage window and high ionic conductivity (Figure 7d-e). The specific discharge capacity of AB5-alloy working electrode in different electrolytes is shown in Figure 7f.…”
Section: Ionic Liquids Electrolytementioning
confidence: 99%
“…ILs have special physicochemical properties and supramolecular structures that have fundamentally altered the concept of liquid. Therefore, ILs have multiple roles in the field of catalysis [ 13 , 19 , 20 ]. They are widely used as media and templates to offer high-performance catalysts because they can dissolve many substances that cannot be dissolved in water or organic solvents [ 20 ].…”
Section: Introductionmentioning
confidence: 99%